2023
DOI: 10.3389/fphys.2023.1166125
|View full text |Cite
|
Sign up to set email alerts
|

Lost in traffic: consequences of altered palmitoylation in neurodegeneration

Abstract: One of the first molecular events in neurodegenerative diseases, regardless of etiology, is protein mislocalization. Protein mislocalization in neurons is often linked to proteostasis deficiencies leading to the build-up of misfolded proteins and/or organelles that contributes to cellular toxicity and cell death. By understanding how proteins mislocalize in neurons, we can develop novel therapeutics that target the earliest stages of neurodegeneration. A critical mechanism regulating protein localization and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 220 publications
0
7
0
Order By: Relevance
“…The effect of S-acylation on trafficking and turnover rate is not only related to membrane partitioning but also to the interplay with ubiquitination ( Abrami et al, 2006 , 2008 ; Hach et al, 2013 ; Yount et al, 2012 ; Zaballa and van der Goot, 2018 ). S-acylation crosstalk with other modifications has been repeatedly reported ( Ahearn et al, 2011 ; Nepal et al, 2023 ; Wang et al, 2023b ; Yan et al, 2022 ), as recently reviewed ( Ramzan et al, 2023 ; Zmuda and Chamberlain, 2020 ). In the context of degradation, it occurs frequently with ubiquitination, which could be mono, multi, or polyubiquitination ( Dikic and Schulman, 2023 ).…”
Section: Introductionmentioning
confidence: 89%
“…The effect of S-acylation on trafficking and turnover rate is not only related to membrane partitioning but also to the interplay with ubiquitination ( Abrami et al, 2006 , 2008 ; Hach et al, 2013 ; Yount et al, 2012 ; Zaballa and van der Goot, 2018 ). S-acylation crosstalk with other modifications has been repeatedly reported ( Ahearn et al, 2011 ; Nepal et al, 2023 ; Wang et al, 2023b ; Yan et al, 2022 ), as recently reviewed ( Ramzan et al, 2023 ; Zmuda and Chamberlain, 2020 ). In the context of degradation, it occurs frequently with ubiquitination, which could be mono, multi, or polyubiquitination ( Dikic and Schulman, 2023 ).…”
Section: Introductionmentioning
confidence: 89%
“…Thus, S-acylation provides an ideal mechanism for quickly redirecting proteins on and off membranes. When S-acylation is disrupted, it leads to protein mislocalization, decreased protein turnover and aggregation 5 .…”
Section: Introductionmentioning
confidence: 99%
“…The use of the tandem LC3 reporter with palmitate treatment, shows a decrease in the number of autophagosomes and an increase in autolysosomes 14 ; again indicating an overall increase in autophagy, and highlighting a link between palmitoylation and autophagy. In addition, we recently showed that the majority of autophagy regulatory genes encode a proteo form that has been detected by low- or high-throughput methods 5 , by comparing the S-acylation database SwissPalm 15 and the Autophagy Regulatory Network 16 .…”
Section: Introductionmentioning
confidence: 99%
“…Similar to myristoylation, S-acylation involves the addition of saturated fatty acids, but via a thioester bond on cysteine residues, making it labile and reversible (Ramzan et al, 2023;Zaballa & van der Goot, 2018). The 16carbon fatty acid palmitate is typically used and, therefore, this modification is more commonly referred to as Spalmitoylation or simply palmitoylation.…”
Section: Introductionmentioning
confidence: 99%